Comparative Effectiveness of Modified Manual and Powered Toothbrushing Interventions in Individuals with Disabilities: A Randomized Controlled Trial Assessing Gingival Health - Abhishek Sinha; Sumit Kumar; Vinod Sargaiyan; Ruby H. Kottapalli; Dheeraj Sharma; Ankit Goyal (Journal of Pharmacy and Bioallied Sciences)
Background: Individuals with disabilities face unique challenges in maintaining optimal oral health due to physical, cognitive, and sensory impairments. Gingivitis is a common oral health problem in this population, necessitating effective interventions tailored to their specific needs. Methods: Participants (n = 162) aged 18–65 years, diagnosed with gingivitis and varying disabilities, were recruited. They were randomly assigned to the modified manual toothbrush group or the powered toothbrush group. The interventions included comprehensive training programs that addressed the specific needs of each group. Gingival index and plaque index scores were recorded at baseline and at 4, 8, and 12 weeks. Patient-reported outcomes, including satisfaction, comfort, and ease of use, were assessed. Statistical analyses were performed, including t-tests, Chi-square tests, and subgroup analyses based on disability types. Results: Baseline characteristics did not demonstrate significant differences between groups. Over 12 weeks, both groups showed a significant reduction in gingival and plaque index scores (P < 0.001). The powered toothbrush group exhibited a slightly greater reduction in gingival inflammation compared to the manual toothbrush group (P = 0.03). Patient-reported results favored the powered toothbrush group in satisfaction (P = 0.02) and ease of use (P = 0.04). Comfort levels did not show significant differences (P = 0.11). Conclusions: This randomized controlled trial provides evidence supporting the effectiveness of modified manual and powered toothbrushing interventions in reducing gingival inflammation among people with disabilities diagnosed with gingivitis.